Cancer Information Seeking and Cancer-Related Health Outcomes: A Scoping Review of the Health Information National Trends Survey Literature. Issue 9 (1st September 2016) - Wigfall, Lisa T.; Friedman, Daniela B.
Abstract : Cancer is a leading cause of death among adults in the United States. Only 54% of U.S. adults reported seeking cancer information in 2014. Cancer information seeking has been positively associated with cancer-related health outcomes such as screening adherence. We conducted a scoping review of studies that used data from the Health Information National Trends Survey (HINTS) in order to examine cancer information seeking in depth and the relationship between cancer information seeking and cancer-related health outcomes. We searched five databases and the HINTS website. The search yielded a total of 274 article titles. After review of 114 de-duplicated titles, 66 abstracts, and 50 articles, 22 studies met inclusion criteria. Cancer information seeking was the outcome in only four studies. The other 18 studies focused on a cancer-related health outcome. Cancer beliefs, health knowledge, and information seeking experience were positive predictors of cancer information seeking. Cancer-related awareness, knowledge, beliefs, preventive behaviors, and screening adherence were higher among cancer information seekers. Results from this review can inform other research study designs and primary data collection focused on specific cancer sites or aimed at populations not represented or underrepresented in the HINTS data (e.g., minority populations, those with lower socioeconomic status).